New precise astrometric observations of Nereid in 2012–2017. (March 2018) - Yu, Y.; Qiao, R.C.; Yan, D.; Cheng, X.; Xi, X.J.; Tang, K.; Luo, H.
Abstract: Nereid is one of the most distinctive natural satellites that we know in the Solar system. The orbit of Nereid is highly eccentric and inclined with respect to the equator of its primary, Neptune. Studying Nereid is one of the inspiring ways to acquire better knowledge of the Solar system. Due to its faintness, the ground-based observations of Nereid have been limited and the observation precisions in the past were generally not high. A total of 150 new observed positions of Nereid in the period 2012–2017 were collected by the 0.8 m reflecting telescope at Xinglong station of National Astronomical Observatory and the 2.4 m reflecting telescope at Lijiang station of Yunnan Astronomical Observatory. Thanks to the high-quality reference catalogue Gaia DR1 and suitable processing methods for images, the precision of our new observations of Nereid is 2–3 times higher than those of the previous observations, and the dispersions of our observations are better than 70 mas. Highlights: Continuous observations of Nereid allow new, more accurate ephemerides to be derived. In this paper, we have presented 150 new precise CCD astrometric observed positions of Nereid in 2012-2017. The dispersions of our observations are better than 70 mas, which is 2~3 times higher than those of previous observations.